Combined Autoimmune Cytopenias Presenting in Childhood. Issue 2 (23rd September 2015) - Al Ghaithi, Ibrahim; Wright, Nicola A.M.; Breakey, Vicky R.; Cox, Kelly; Warias, Ashley; Wong, Tiffany; O'Connell, Colleen; Price, Victoria
Abstract: Background: Pediatric patients with chronic and/or refractory autoimmune multi‐lineage cytopenias present challenges in both diagnosis and management. Increasing availability of diagnostic testing has revealed an underlying immune dysfunction in patients previously diagnosed with Evans Syndrome. However, the data are sparse and the majority of patients are adults. Procedure: We performed a retrospective chart review to document the natural history of 23 pediatric patients with autoimmune multi‐lineage cytopenias followed at three tertiary care pediatric hematology clinics. Results: Investigations revealed seven patients (30.4%) with an autoimmune lymphoproliferative‐like syndrome and six patients (26.1%) with other primary immunodeficiencies. Only one (4.3%) patient was suspected to have systemic lupus erythematosus and six patients (26.1%) had other types of autoimmunity. Treatment consisted of immunosuppressive therapy, intravenous gammaglobulin, and splenectomy. Supportive care included granulocyte‐colony stimulating factor, and blood product transfusions. Two patients (8.7%) died. Complete remission was achieved in 3 patients (13.0%); of the remaining, 14 patients (60.9%) had chronic immune thrombocytopenic purpura, 10 patients (43.5%) chronic autoimmune neutropenia, and 4 patients (17.4%) chronic autoimmune hemolytic anemia with a median follow up of 5 years (2 months–12 years). Conclusions: These data suggest that pediatric patients presenting with autoimmune multi‐lineage cytopenias should undergo investigation for underlying immune dysregulation, including autoimmune lymphoproliferative syndrome, other primary immunodeficiencies and autoimmune disorders. The development of an international registry for such patients is imperative to improve the understanding of their complex natural history. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.